Muscle activation during lower body resistance training - Ebben, W. P.; Feldmann, C. R.; Dayne, A.; Mitsche, D.; Alexander, P.; Knetzger, K. J. (International Journal of Sports Medicine, 2009)
This study evaluated the biceps femoris (BF), rectus femoris (RF), and vastus lateralis (VL) activation and activation ratios of a variety of resistance training exercises characterized by knee extension, and determined if subject strength or gender affects these variables. The exercises evaluated included the leg extension, squat, deadlift, lunge, and step up. Subjects included 20 athletes and recreationally active college students. Electromyography (EMG) of the muscles expressed as a percentage of maximum voluntary isometric contraction (MVIC), as well as the BF to RF and BF to VL EMG ratio, were determined for each exercise. There was no significant interaction between gender and exercise type for the RMS EMG of the BF (p = 0.67), RF (p = 0.53), or VL (p = 0.06). Main effects were found for the RMS EMG of the BF (p = 0.00), RF (p = 0.00), and VL (p = 0.00), as well as the RMS EMG of the BF to RF activation ratio (p = 0.00) and BF to VL activation ratios (p = 0.003), between exercises. Peak RMS EMG was also assessed. Post hoc analysis identified specific differences in muscle activation and ratios between exercises. Clinicians should consider the magnitude of muscle activation and activation ratios when prescribing hamstring and quadriceps exercises.